Penetrating Iron Rod Wound of the Lumbar Spine Causing Cauda Equina Syndrome in a Child: Case Report and Review of the Literature - Ilunga, Roger Mulumba; Barry, Louncény Fatoumata; Ndongo, Mouhamadou Moustapha; Cisse, Yakhya; Atakla, Hugues Ghislain; Wague, Daouda; Faye, Mohameth; Ba, Momar Code (Indian Journal of Neurotrauma, 2023)
The authors report the case of a 10-year-old child who was admitted to the emergency room with a penetrating lumbar spinal injury caused by an iron rod, which occurred accidentally during a recreational activity. The clinical presentation was a ponytail syndrome with paraparesis and cerebrospinal fluid discharge from the lumbar penetration point of the iron rod. The lumbar X-ray and computed tomography (CT) scan performed in the emergency room revealed the iron rod penetrating the spinal canal through the lamina of the L3 vertebra on the left, requiring urgent surgical management, consisting of laminectomy of L3 allowing the removal of the iron rod and repair of the dura mater without any damage to the roots of the cauda equina. The evolution was favorable with complete motor recovery at 3 months follow-up.
Keywords: iron rod; cauda equina; lumbar spine; penetrating wound; child